Performance analysis on internal combustion engine of spark ignition (SI) type on Perodua engines / Nasrol Mansor - Mansor, Nasrol (2003)
Nowadays it is important to analyze several internal combustion engine parameters. These parameters are important in order to ensure that the engine runs smoothly, at top performance and emit less pollutant to environment. The main parameters that are usually considered are Break-Power and Fuel Consumption. Every vehicle owners are very particular about this thing. They want a high performance engine with an economically fuel consumption. I, as a final year student under the tutelage of Prof. Madya Dr. Rahim Atan have to perform a field evaluation and analysis of engine performance by doing testing for different types of engine at PERODUA ENGINE MANUFACTURING SDN. BHD.The test is based on five types of engines, Kancil, Kenari, Kelisa, Rusa and Kembara. Some adjustments are made to the engines to ensure the engines are able to run consistently and at performance standard. Service was done to the engines, where we changed several parts that have worn-out, such as the piston ring, crank bearing and connecting rod bearing. All the testing is run in the QA department lab at PERODUA ENGINE MANUFACTURING SDN. BHD. Results obtained from the testings are used to calculate the parameters mentioned earlier. The analysis and evaluation have also been done by which we make recommendations at which ignition timing, emission level and fuel consumption to be set to make the engines run at top performance.